Genetic variability of E. histolytica strains based on the polymorphism of the SREHP gene using nested PCR-RFLP in Erbil, North Iraq - Mahmood, Shler Akram Faqe; Mustafa Bakr, Hawri (Cellular and Molecular Biology, 2020)
E. histolytica is an intestinal parasite that causes asymptomatic infection mostly; however, it may also cause amoebic dysentery and liver abscess. Molecular identification is required in epidemiological studies due to the presence of morphologically identical nonpathogenic species. Therefore, this study was conducted to first evaluate the prevalence rate of E. histolytica among symptomatic individuals of Erbil city, and to investigate the genetic diversity of the parasite in a limited geographic area. Accordingly, a total of 2026 samples were examined microscopically, and confirmed by nested PCR for 18s rRNA gene. The results showed that the prevalence rate of E. histolytica was 1.97% (40 samples) among symptomatic patients. The SREHP gene was used as a marker to show the genetic polymorphism of E. histolytica; however, to compare the genetic diversity of symptomatic with asymptomatic isolates, 57 asymptomatic samples were obtained from our previous study. The amplified products of the SREHP gene were digested by AluI endonuclease, and DNA banding patterns were analysed. Results showed 29 different DNA patterns among the 97 symptomatic and asymptomatic samples, 62 of which shared similar DNA patterns. However, 8 different DNA patterns were observed among asymptomatic samples, whereas 15 distinct patterns were observed among symptomatic isolates. In conclusion, this study found that the prevalence rate of E. histolytica was relatively low; relatively high genetic diversity was observed in a restricted endemic area; with higher rates of variability in symptomatic rather than in asymptomatic isolates, indicating a possible correlation between the genotype of E. histolytica and their clinical outcome.